2014
DOI: 10.1111/aji.12281
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia muridarum Infection Associated Host MicroRNAs in the Murine Genital Tract and Contribution to Generation of Host Immune Response

Abstract: Problem Chlamydia trachomatis (CT) is the leading sexually transmitted bacterial infection in humans and is associated with reproductive tract damage. However, little is known about the involvement and regulation of microRNAs (miRs) in genital CT. Methods We analyzed miRs in the genital tract (GT) following C. muridarum (murine strain of CT) challenge of wild type (WT), and CD4+ T cell deficient (CD4−/−) C57BL/6 mice at days 6 and 12 post challenge. Results At day 6, miRs significantly downregulated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(59 citation statements)
references
References 85 publications
8
51
0
Order By: Relevance
“…Transcriptome-wide or sequencing approaches have revealed the role for specific immune genes and associated pathways following infection with Ct-plasmid-sufficient and -deficient strains (Porcella et al 2015; Carlson et al 2008; Ferreira et al 2013; Qu et al 2015). Similarly, regulatory genetic species, namely microRNAs of bacterial and host origin have revealed the role(s) in growth and cellular function following infection (Derrick et al 2013; Furuse et al 2014; Gupta et al 2015; Yeruva et al 2014; Igietseme et al 2013). Proteomic studies have identified immunodominant, T- and B cell chlamydial antigens involved in primary infection and vaccination (Cruz-Fisher et al 2011; Wang et al 2010; Karunakaran et al 2015; Picard et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome-wide or sequencing approaches have revealed the role for specific immune genes and associated pathways following infection with Ct-plasmid-sufficient and -deficient strains (Porcella et al 2015; Carlson et al 2008; Ferreira et al 2013; Qu et al 2015). Similarly, regulatory genetic species, namely microRNAs of bacterial and host origin have revealed the role(s) in growth and cellular function following infection (Derrick et al 2013; Furuse et al 2014; Gupta et al 2015; Yeruva et al 2014; Igietseme et al 2013). Proteomic studies have identified immunodominant, T- and B cell chlamydial antigens involved in primary infection and vaccination (Cruz-Fisher et al 2011; Wang et al 2010; Karunakaran et al 2015; Picard et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Nigg V infection results in a higher bacterial load; thus, it is possible that increased inflammatory responses and miRNA expression are due to a higher replicative capacity of the chlamydiae. Interestingly, Gupta et al (45) showed no overall differences in miRNA expression with three different doses (5 ϫ 10 4 , 5 ϫ 10 5 , and 5 ϫ 10 6 ), suggesting that Nigg V interaction with host cells is different from that of Nigg A in terms of regulating host miRNA expression and is not necessarily related to numbers of microorganisms. Regardless of the replicative capacity of bacteria, our results suggest that miRNAs expression regulates the inflammatory response, thus dictating the pathological outcome.…”
Section: Discussionmentioning
confidence: 97%
“…The results showed that miRNAs were differentially expressed and cytokine responses were significantly upregulated in Nigg V -infected mice, correlating with oviduct pathology. A study by Gupta et al (45) showed significant downregulation of miR-125b-5p, miR-16, miR-214, miR-23b, miR-135a, miR-182, miR-183, miR-30c, and miR-30e on day 6 following genital infection of mice. More recently, it has been demonstrated that during ocular C. trachomatis infection, upregulation of miR-155 and downregulation of miR-184 correlated with conjunctival inflammation (43).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, we reported alteration of host microRNA (miR) profiles during the early stage (day 6) of C. muridarum infection . These short, non‐coding RNA species modulate gene function post‐transcriptionally by direct binding to target gene mRNA, influencing biological processes including immune function and reproduction, and constitute potential biomarkers for genital C. trachomatis infection in humans .…”
Section: Introductionmentioning
confidence: 99%